POEMA PEDAGÓGICO: UMA EXPERIÊNCIA EDUCACIONAL INOVADORA, DESENVOLVIDA POR MAKARENKO E SUA RELAÇÃO COM O MARXISMO | Pedagogical Poem: an innovative educational experience, fostered by Makarenko and his affinity with Marxism (Trabalho & Educação, 2018)
Antón Semiónovirch Makarenko was born in Bielopie, Krákov, in 1888, and died in 1939. He lived through the Russian Revolution of 1917, in which the Bolsheviks, headed by Lenin, appointed him as leader of the Council of People’s Commissars and overthrew Tsar Nicholas II. In this historical period, Russia faced two hecatombs, namely, World War I and the mentioned Revolution and, consequently, millions of children and, above all, young people engaged in prostitution, theft, and murder, among other felonies. Amidst such context, the educator on the agenda was designated as director of the Gorky Colony, near Poltava. In his mission he was heavily influenced by Lenin, mainly concerning the relevance ascribed to arts, aesthetics, and ethics towards the shaping of a new man who should be inserted in a new society. Gorky was also a great example for the educator in question, markedly through his literary, active and political romanticism, as well as by his view of intellectuals - as political and social organizers. Makarenko’s major works include The Pedagogical Poem (1925-1935), The Book for Parents (1937) and Flags on the Battlements (1938). In The Pedagogical Poem, the given author presents his educative proposal, largely affected by Marxist ideas, formulated in the practice of his position as Gorky Colony director. His work with marginal orphans was guided by the following principles: a) omnilateral formation; b) connection between work and education; c) teaching authority and discipline; d) shared management between teachers and students. His professional performance in this colony has been acknowledged both by the Union of Soviet Socialist Republics (USSR) and worldwide.___Antón Semiónovirch Makarenko nasceu em Bielópie, província de Krákov, em 1888 e morreu em 1939, tendo assim, vivido na época da Revolução Russa de 1917, na qual os bolcheviques, liderados por Lenin, destituíram do poder o czar Nicolau II e o proclamaram como líder dos Comissários do I Conselho Comunitário do Povo. Nesse período histórico, a Rússia enfrentava duas hecatombes, ou seja, a I Guerra Mundial e a mencionada Revolução e, em decorrência, milhões de crianças e, sobretudo, jovens estavam se prostituindo, roubando, matando, entre outros delitos. Assim, nesse cenário, o educador em pauta foi indicado para ser gestor da Colônia de Gorki, próxima de Poltava. Nessa missão, foi muito influenciado por Lenin, sobretudo no que tange à importância que deveria ser conferida à arte, à estética e à ética, para a formação de um novo homem, que deveria se inserir em uma nova sociedade. Gorki foi, também, uma grande referência para o educador em pauta, notadamente através do seu romantismo literário, ativo e político e, sobretudo, pela sua visão do intelectual, como organizador político e social. As principais obras de Makarenko são o Poema Pedagógico, Bandeiras nas Torres e Livro dos Pais. No Poema Pedagógico, o autor em pauta apresenta sua proposta educativa, de inspiração marxista, desenvolvida na prática de sua atuação como diretor, na Colônia de Gorki. Seu trabalho, sobretudo com jovens em situação de marginalidade, se norteou por estes princípios: formação omnilateral; relação entre trabalho e educação; autoridade docente e disciplina; coletivo como gestão compartilhada entre docentes e discentes. Seu trabalho nessa Colônia foi reconhecido tanto pela União das Repúblicas Socialistas Soviéticas (URSS), quanto no âmbito internacional.